Resources for teaching mathematics, 14-16 - Foster, Colin, 1973- (Resources for teaching., 2010)
This resource contains 70 complete lesson plans with complementary worksheets for the students, specifically designed for GCSE level maths. This book contains 70 ready-to-use maths lessons suitable for the new GCSE Mathematics curriculum. The lesson plans contain objectives from both the D-G range and the A-C range to make them adaptable for different sets or for use in a mixed-ability context. Each lesson consists of a left-hand page for the teacher, outlining the structure of the lesson from a starter through to homework, and a right-hand photocopiable pupil worksheet to provide a setting in.